CONTRIBUIÇÃO AO ESTUDO DA MATURAÇÃO DA GÔNADA FEMININA DO "CAMARÃO-ROSAââ‚¬Â (Penaeus paulensis PÉREZ FARFANTE, 1967) - G. de S. Neiva; T.U. Worsmann; M.N. Oliveira; H. Valentini (Boletim do Instituto de Pesca)
During this study pink shrimp gonadal maturity was divided into four stages based on macroscopic characteristics observed during their development. This research describes the main ovarian characteristics observed from both macroscopic and microscopic examinations. It was concluded that the criteria of gonada1 maturity established in this paper were justified on biological grounds.